Exploring teaching and learning German as a foreign language at a South African institution of higher education: blended learning and collocations - Ortner, Gwyndolen Jeanie (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
German Studies students at Rhodes University have normally never studied the German language before enrolling for the first-year course and face the challenge of a fairly rapid linguistic advancement, in a context with very limited exposure to the foreign language outside the classroom. Free writing is an area which students find particularly challenging as it requires students to syndissertatione grammatical and vocabulary knowledge. Furthermore, South African students are often underprepared for the challenges they face at university regarding language, technology and finance, as they try to to assimilate to the academic environment and gain epistemological access to their various subjects, in this case, language acquisition and the attendant modules of translation, literature and cultural studies. The use of technology in teaching and learning, known as blended learning, is said to produce better results than face-to face teaching alone, through creating opportunities for more autonomous student learning. Scholars of instructed second-language acquisition also suggest using technology to improve language instruction. One particular area which is gaining ground is teaching students collocational structures through exploring large language corpora, to improve students' language competencies such as writing fluency. However, both blended learning practices and corpus-based teaching practices suggested by scholars are often not reported on in a particular teaching and learning context, taking into account factors such as institutional infrastructure, student and staff backgrounds and preparedness, and larger socio-political factors. Thus, it remains unclear how these practices (blended learning and corpus-based teaching of collocations) may be integrated into standard urricula, particularly for languages other than English, which have been severely under-researched. The purpose of this research is to take a context-based approach to language teaching and thereby investigate current blended learning practices for German Studies at Rhodes University in South Africa and explore through an action research approach how to integrate collocational awareness into the curriculum, within the blended learning model. Insights from corpus linguistics guide an adaptation of teaching practice, helping students develop skills to aid with writing fluency, seeking to make the patterned nature of language salient to our students. This is undertaken in a scaffolded way, within the curriculum, making use firstly of the texts to which students are exposed in the textbook (comprehensible input) as a source of collocational examples, and following this by making use of reallife language data from an online German corpus, DWDS. Findings from the study reveal a number of best practices related to the use of blended learning and teaching collocations in context of the German foreign language curriculum at a South African institution of higher education.
Keywords: German language -- Study and teaching (Higher) -- South Africa; German language -- Study and teaching (Higher) -- Foreign speakers -- South Africa; German language -- Study and teaching (Higher) -- English speakers -- South Africa; Rhodes University -- Students; Rhodes University. German Studies